2013
DOI: 10.4236/ijg.2013.49124
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Porosity and Density of Calcarenite Rocks from P-Wave Velocity Measurements

Abstract: Petrophysical proprieties such as porosity, density, permeability and saturation have a marked impact on acoustic proprieties of rocks. Hence, there has been recently a strong incentive to use new geophysical techniques to invert such properties from seismic or sonic measurements for rocks characterization. The P-wave velocity, which is non-destructive and easy method to apply in both field and laboratory conditions, has increasingly been conducted to determine the geotechnical properties of rock materials. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 16 publications
(23 reference statements)
1
11
0
Order By: Relevance
“…Number of researchers (Kahraman, 2001;Kahraman, 2002;Yasar and Erdogan, 2004;Kilic, 2006;Khandelwal and Ranjith, 2010;Fener, 2011;Rahmouni et al, 2013;Zulfahmi, 2013;Arman et al, 2014;Parent et al, 2015;Arman et al, 2016) have already studied the possible relationships between rock properties and SV values and found that SV values are somehow related with rock properties.…”
Section: Introductionmentioning
confidence: 99%
“…Number of researchers (Kahraman, 2001;Kahraman, 2002;Yasar and Erdogan, 2004;Kilic, 2006;Khandelwal and Ranjith, 2010;Fener, 2011;Rahmouni et al, 2013;Zulfahmi, 2013;Arman et al, 2014;Parent et al, 2015;Arman et al, 2016) have already studied the possible relationships between rock properties and SV values and found that SV values are somehow related with rock properties.…”
Section: Introductionmentioning
confidence: 99%
“…In general, we observe that the high value of the P-wave velocity is obtained for the samples saturated and the low value is obtained for dry samples. The authors Boulanouar et al [7], Guéguen et al [17] and Rahmouni et al [18] compared the velocities P-wave in dry and saturated with water. They generally observed that V P (dry) < V P (saturated).…”
Section: Resultsmentioning
confidence: 99%
“…The UCS can be also related to sonic pulse velocity [26]. By regression analysis equation of coefficient determination (R 2 ) the best appropriate relationships were acquired to be well signified by linear regression [17], it enhanced predictable UCS values concluded a broader variety of Sonic Pulse Velocity values . It is possible with Sonic Pulse velocity range of saturated samples from 26.2 to 49.0 km/s and for dry sample the range from 28.4 to 55.8 km/s.…”
Section: Relationship Of Ucs and Sonic Pulse Velocitymentioning
confidence: 99%
“…Misleading result produce for high and low values of Sonic Pulse velocity. Therefore, not be used to validate .The lithology is a estimated aspect for the intention of P-wave velocity [17]. In sedimentary rocks Pwave velocity are great for carbonates and at low P-wave velocity of the sandstones [17].…”
Section: Relationship Of Ucs and Sonic Pulse Velocitymentioning
confidence: 99%
See 1 more Smart Citation